Individual Approach to Choosing Tactics for Treatment of Rectovaginal Fistulas (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
to improve treatment outcomes in patients with rectovaginal fistulas.The results of surgical treatment of 23 patients with rectovaginal fistulas were assessed. Two categories of surgical interventions were used. 11 patients underwent excision of fistulas with subsequent layer-by-layer suturing of the surgical wound tightly without the use of components of sphincter levatorplasty. In the remaining 12 patients, the operation was supplemented by segmental proctoplasty, plastic surgery of the vaginal wall with a mobilized mucosal-submucosal flap after performing anterior sphincter levatorplasty.In the first group of patients, 1 relapse of the disease was registered. In the second group of patients, no relapses were noted. the use of the technique of radical excision of the rectovaginal fistula, supplemented by anterior sphincter levatorplasty, is the most promising method for reducing the number of postoperative complications and relapses of the disease by restoring the layered structure of the rectovaginal septum.